Contriving emotional resilience through spirituality in the light of Vedanta - Narasimhan, Pavithra Lakshmi; Saputra, Heru (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2023)
This study examines the Indian perspective on emotions, focusing on the concept of Gunas or Subjective Experiences. Indian Philosophies emphasize the transient nature of emotions and advocate for achieving emotional equilibrium through allegiance to a higher power and surrender. The study concludes that spirituality plays a crucial role in shaping individuals' emotional experiences, contributing to improved mental well-being and reduced narcissistic tendencies. Religious practices foster a sense of security and trust in a "superior being", while emotions involve the feelings experienced towards God or the Divine. Resilience, defined as the ability to adapt in the face of difficulties, is closely linked to these components. The hypothesis posits that an affinity towards the concept of God optimizes both emotions and resilience, fostering well-being across physical, psychological, emotional, and social domains. By investigating the interplay between emotions, religion, and resilience from an Indian perspective, this study contributes to a deeper understanding of their complex relationship and their impact on mental health. The utilization of library research allows for an in-depth exploration of relevant literature and philosophical texts. The insights derived from this research have the potential to inform mental health interventions and promote holistic well-being in diverse cultural contexts. By recognizing the significance of religious and spiritual factors in emotional experiences and resilience, practitioners can tailor interventions that address the specific needs of individuals within different cultural and religious frameworks, ultimately enhancing their overall mental well-being.